Implementation of Automation and System Integration in The Weighing Process and Documentation of Coal Shipments Using The FOBMV Method At PT XYZ - Arli, Faris Zharfan; Mulyono, Nur Budi (Dinasti International Journal of Education Management and Social Science, 2025)
This research investigates operational challenges in the mining industry, specifically the weighing and documentation of coal shipments at PT XYZ. The process previously relied on manual data entry across three separate systems, resulting in recurring problems of data inaccuracy, process inefficiency, and excessive workload that disrupted operations and delayed managerial decision-making. The study aims to analyze the root causes of these issues, design a practical solution, and evaluate its impact. A mixed-method approach was applied, combining interviews, field observations, and quantitative measures such as error rates, process cycle efficiency, and Full-Time Equivalent calculations. The proposed solution, designed through a user-centered design framework, introduced automation via RFID-based dump truck identification, automatic generation of delivery documents, and integration of weighbridge data across internal and external applications. Implementation reduced errors by 86%, improved efficiency more than fourfold, and decreased workload by 80%, allowing a single operator to manage the process effectively. The findings confirm that automation and system integration significantly improve the accuracy, efficiency, and reliability of coal shipment documentation, demonstrating how digital interventions can enhance both operational performance and strategic decision-making in mining logistics.